Negative correlation of patient-specific quality assurance failure rates with Monitor Units for Volumetric-Modulated Arc Therapy - Murshed Hossain; Nathan M Papalia (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2020)
Purpose: Failure rates of patient-specific Quality Assurance tests in intensity modulated external beam radiation therapy are known to be correlated with both the degree of modulation and Monitor Units (MU). Our goal is to examine if this remains true for Volumetric-Modulated Arc Therapy (VMAT). Methods: We have analyzed the pass rates for 118 VMAT patient-plans for prostate cancer by examining the Gamma Index (GI) of two-dimensional portal dose distributions. Results: We found that the failure rates based on GI is negatively correlated with MU with correlation coefficients of -0.28 and -0.35 at 2%-2mm and 3%-3mm levels respectively. Lower MU plans have generally lower pass rates for the VMAT. This contrasts with the traditional results that the failure rates increase with the degree of intensity modulation. This difference is due to the manner of VMAT delivery. Conclusions: Lower MU VMAT plans generally have lower pass rates.